2022
DOI: 10.1002/dc.25017
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐needle aspiration cytology in soft tissue tumors—5‐year institutional experience

Abstract: Introduction Fine‐needle aspiration cytology (FNAC) forms one of the first‐line investigations in the evaluation of tumors in modern era. Its role in diagnosing soft tissue tumors (STT) has been well established. However, the morphological overlap and biological heterogeneity of STT pose a morphological diagnostic challenge. Aims To evaluate the scope of FNAC in diagnosis and categorization of STT and to correlate the cytological features with histological findings wherever available, and to analyze the reason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…and Rakheja et al , who found benign tumours to be 93.5%, 95.3%, 82.3% and 94.2% respectively. [ 7 - 9 , 12 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and Rakheja et al , who found benign tumours to be 93.5%, 95.3%, 82.3% and 94.2% respectively. [ 7 - 9 , 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…who observed a sensitivity, specificity, PPV, NPV and diagnostic accuracy of 95.2%, 100%, 100%, 96.4% and 97.9% respectively. [ 12 ] Soni et al . observed an accurate characterization in 77.14% cases between the cytological and final histopathological diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…There is a substantial volume of literature establishing the utility of FNAB in differentiating benign from malignant tumours, with a sensitivity varying from 84% to 100%, a specificity varying from 83% to 98% and a positive predictive value ranging from 84% to 99%. However, there is considerable variation in the attitude among pathologists and clinicians regarding the role of FNAB as a primary diagnostic modality for the evaluation of clinically or radiologically “suspicious” soft tissue masses 1–9 . The reasons for this include the growing number and complexity of soft tissue tumour types, including sarcomas, with overlapping morphological, immunohistochemical (IHC) and occasionally molecular features 10 .…”
Section: Pattern Immunohistochemistry Molecular/genetic Testmentioning
confidence: 99%
“…However, there is considerable variation in the attitude among pathologists and clinicians regarding the role of FNAB as a primary diagnostic modality for the evaluation of clinically or radiologically "suspicious" soft tissue masses. [1][2][3][4][5][6][7][8][9] The reasons for this include the growing number and complexity of soft tissue tumour types, including sarcomas, with overlapping morphological, immunohistochemical (IHC) and occasionally molecular features. 10 In contrast to core needle and excision biopsy specimens, there has been a tendency to utilise direct FNAB smears and cell blocks less frequently for these ancillary techniques, leading to a lower percentage (reported as 25% to 47%) of tumours being precisely subtyped.…”
mentioning
confidence: 99%
See 1 more Smart Citation